Room-Temperature Ionic Liquids in Glycoscience: Opportunities and Challenges - Rajkhowa, Sanchayita; Kale, Raju R.; Sarma, Jyotirmoy; Kumar, Abhijeet; Mohapatra, Prabhu P.; Tiwari, Vinod K. (Current Organic Chemistry, 2021)
Carbohydrates are fascinating molecular scaffolds known for their diverse applications in chemistry, biology, medicine, technology, and materials science. In addition, owing to the notable features of Room-Temperature Ionic Liquids (RTILs) such as high-yield, short reaction time, simple handling, excellent recyclability, and environmentally benign nature, they have been extensively utilized as green solvents, catalysts, or both in a wide range of organic transformation methodologies for easy access of a diverse range of biologically relevant molecules. This review highlights the importance of RTILs that offer promising solutions in glycoscience, particularly in relevance to the dissolution, functionalization, glycosylation, and modification of carbohydrates as well as their challenges, impact, and future perspectives.
Keywords: green chemistry